The Role of Glia in Canine Degenerative Myelopathy: Relevance to Human Amyotrophic Lateral Sclerosis - Golubczyk, Dominika; Malysz-Cymborska, Izabela; Kalkowski, Lukasz; Janowski, Miroslaw; Coates, Joan R; Wojtkiewicz, Joanna; Maksymowicz, Wojciech; Walczak, Piotr (Molecular neurobiology, 2019)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by progressive degeneration of motor neurons and grim prognosis. Over the last decade, studies on neurodegenerative diseases pointed on the role of glia in supporting the proper function of neurons. Particularly, oligodendrocytes were shown to be essential through myelin production and supplying axons with energy metabolites via monocarboxylate transporters (MCT). We have used dogs with naturally occurring degenerative myelopathy (DM) which closely resembles features observed in human ALS. We have performed two types of analysis of spinal cord tissue samples: histology and molecular analysis. Histology included samples collected from dogs that succumbed to the DM at different disease stages, which were compared to age-matched controls as well as put in the context of young spinal cords. Molecular analysis was performed on spinal cords with advanced DM and age-matched samples and included real-time PCR analysis of selected gene products related to the function of neurons, oligodendrocytes, myelin, and MCT. Demyelination has been detected in dogs with DM through loss of eriochrome staining and decreased expression of genes related to myelin including MBP, Olig1, and Olig2. The prominent reduction of MCT1 and MCT2 and increased MCT4 expression is indicative of disturbed energy supply to neurons. While Rbfox3 expression was not altered, the ChAT production was negatively affected. DM in dogs reproduces main features of human ALS including loss of motor neurons, dysregulation of energy supply to neurons, and loss of myelin, and as such is an ideal model system for highly translational studies on therapeutic approaches for ALS.